2018
DOI: 10.33549/physiolres.934047
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Lung Inflammation, Oxidative Stress and Apoptosis by the PDE4 Inhibitor Roflumilast in Experimental Model of Acute Lung Injury

Abstract: Damage of alveolar-capillary barrier, inflammation, oxidative injury, and lung cell apoptosis represent the key features of acute lung injury (ALI). This study evaluated if selective phosphodiesterase (PDE)-4 inhibitor roflumilast can reduce the mentioned changes in lavage-induced model of ALI. Rabbits with ALI were divided into 2 groups: ALI without therapy (A group) and ALI treated with roflumilast i.v. (1 mg/kg; A+R group). One group of healthy animals without ALI served as ventilated controls (C group). Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Expression is triggered by epithelial damage, microbial invasion, and allergen sensitization. Its inhibition is a promising target for suppressing inflammatory responses ( Contreras et al., 2017 ) as was demonstrated for roflumilast in an animal model of acute lung injury ( Kosutova et al., 2018 ). PDE4 inhibitors are well-characterized pharmaceutical agents with a broad range of anti-inflammatory activities also in various inflammatory conditions including allergic diseases ( Howell et al., 2018 ).…”
Section: Pdes As a Therapeutic Targetmentioning
confidence: 99%
“…Expression is triggered by epithelial damage, microbial invasion, and allergen sensitization. Its inhibition is a promising target for suppressing inflammatory responses ( Contreras et al., 2017 ) as was demonstrated for roflumilast in an animal model of acute lung injury ( Kosutova et al., 2018 ). PDE4 inhibitors are well-characterized pharmaceutical agents with a broad range of anti-inflammatory activities also in various inflammatory conditions including allergic diseases ( Howell et al., 2018 ).…”
Section: Pdes As a Therapeutic Targetmentioning
confidence: 99%
“…However, the excessive and inadequate apoptosis can lead to the pathogenesis of diseases. It has been suggested that ALI/ARDS is associated with a dysbalanced lung cell apoptosis ( Kosutova et al, 2018 ; Wu Y. et al, 2020 ). The pulmonary epithelial cells are exposed and susceptible to multiple environmental stress and internal responses, in particular, virus infection is an important stimulus that triggers apoptosis of epithelial cells ( Yeung et al, 2016 ; Khatri et al, 2018 ).…”
Section: Anti-apoptosismentioning
confidence: 99%
“…Viability and total number of cells in BALF were determined by cell analyzer Countess (Invitrogen, USA). Total protein in BALF was measured by methods of Bradford (1976), as published by us earlier (Kosutova et al 2018).…”
Section: Analysis Of Cells and Total Protein Content In Balfmentioning
confidence: 99%
“…NO reacts with superoxide anions to form a highly potent oxidant peroxynitrite which together with other oxidants damages proteins, lipids, and nucleic acids. The complex action of inflammatory processes and oxidative effects of reactive oxygen and nitrogen species (RONS) finally leads to a disruption of the alveolar-capillary barrier with subsequent formation of interstitial and alveolar edema and progression of lung injury (Lamb et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation